Autoestima y su influencia en el rendimiento académico de una niña de 13 años - Parreño Parreño, Ana Gabriela (2020)
With the intention of obtaining favorable results, this case study was carried out, which as a general objective is to determine how self-esteem influences the academic performance of a 13-year-old girl, the non-assessment itself was observed within the clinical observation same, negative thoughts towards his person, another of the techniques applied is the Rosemberg Self-Esteem Scale test, for which it has been designed to measure the levels of self-esteem whose results of low self-esteem and the Beck depression scale test which evaluates depression levels, obtaining a moderate depression episode assessment. The analysis performed to the P.I. Through the interviews applied and its indications of low self-esteem, symptoms, according to the manual of the classification of mental disorders of the ICD-10, it was concluded that the patient is in an episode of moderate depression. In which it was programmed as a proposal to execute a therapeutic plan through cognitive behavioral therapy, followed by rational emotional therapy, each one must fulfill at least 6 sessions with their respective techniques so that the patient achieves a better quality of life.